Comparison of take-off dynamics in the forward handspring followed by forward somersault tuck on the floor - Abdel-Baser, E. A. (World Journal of Sport Sciences, 2010)
The aim of this study was to identify the mechanical factors of take-off associated with identical performance for both forward handspring (HN.S.) and forward somersault tuck (F.SS.T.) on the floor. The research sample included four women gymnasts of high performance from Somuha Club in Alexandria, Egypt. A video camera filming at a nominal rat of 60 Hz was used to record the performance of the two mentioned skills. Each of (HN.S. and F.SS.T.) was analyzed with the aid of a Simi motion analysis system. The most important results of the two skills tactics revealed that it consists of two essential factors as follows: first, Motion output, which determines the height of the geometric path for center gravity (CG.) through the flight phase. It has a direct effect on the level of motion performance for the pre and post-skill in the kinematic chains. Second, the position factor which is referred to as the composition various body organs take in both the moment of performing the take-off andfinishing in the previous skill, which considers the moment of take off to perform the subsequent skill either by both feet or hands. It can be identified by the amount of body angles and changes that occur in this amount at both kinematic path points during the build.